Pasta de pescado desodorizado para elaboración de salchicha de pescado vida útil y aceptabilidad - Rivera Ibañez, William Alfredo (2012)
The preparation of sausages has since antiquity a way to preserve the fresh meat faenada raw material in order to retain it longer. With technological advancement have been developing new products easily performed thus decreasing processing times of meals such as sausages. In preparing this research had the following objectives: Harnessing deodorized fish paste guapuro species (Polydactylus approximans) in sausage making. Evaluation of life and acceptability of the sausage produced. This work was carried out in the laboratory of Technology and Processing of Aquatic Organisms, Faculty of Agricultural Sciences at the Technical University of Machala, which is located on the farm St Agnes Avenue June 25 Km 5 ½ way to passage in the coordinates 03 º 16 '00 "south latitude and 79 º 57' 31" west longitude. Sensory analysis was performed on 80 people who were not expert tasters were taken into consideration factors such as smell, color, taste, texture, and acceptability reached the following conclusions: Harnessing Guapuro fish paste, in making sausages, was successful and easy to prepare. The tastings showed unfavorable acceptance for sausages made ​​from fish in both formulations. In the physicochemical quality difference was found in pH and fat, being higher meat content in F2 (concentration 20% pork) F1 pH is lower and with a low meat content (pork concentration 10%) obtained a higher pH. Both formulations are within optimal ranges established under SFAS INEN